Statistical digital signal processing and modeling - Hayes, Monson H. (Wiley, 1996)
Introduction - Background - Discrete-time random processes - Signal modeling - The Levinson recursion - Lattice filters - Wiener filtering - Spectrum estimation - Adaptive filtering - Appendix.